2018
DOI: 10.1080/21693277.2018.1509742
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and organisational team formations for effective Lean transformations

Abstract: Teamwork is considered essential for effective Lean organisations. However, how and why are teams formed during a successful Lean transformation relative to changes in organisational structure? Constructs for variables and factors that influence formation of teams, during and after Lean transformation maturity, were identified. The research employed a purposively sampled case study with three questionnaires, focus groups, interviews and multiple linear regression. Self-directed teams become flow-line or cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Employee engagement and participation are fundamental to reaping the full benefits of TPS implementation (Liker, 2004). Vries and Poll (2018) found that the more progress is made in lean processes, the more engagement and participation there is, resulting in more teamwork. 15 of the 19 lean techniques have a very significant positive coefficient.…”
Section: Lean Kaizen Randdmentioning
confidence: 99%
See 1 more Smart Citation
“…Employee engagement and participation are fundamental to reaping the full benefits of TPS implementation (Liker, 2004). Vries and Poll (2018) found that the more progress is made in lean processes, the more engagement and participation there is, resulting in more teamwork. 15 of the 19 lean techniques have a very significant positive coefficient.…”
Section: Lean Kaizen Randdmentioning
confidence: 99%
“…Since the 1960s, Japan has also proposed a system similar to the Balanced Scorecard BSC as a well-integrated system for deploying lean strategies. The system was named Hoshin Kanri (Policy Management HK) and has been implemented by companies worldwide as an important component of lean transformation strategies (Chiarini & Vagnoni, 2016;Vries and Poll, 2018). The company uses PD (strategic deployment) and DM (daily management), Quality Insurance (QI) stories, and simple Quality Control (QC) tools.…”
Section: Lean Kaizen Randdmentioning
confidence: 99%
“…So, there is another concern that arose just because of alterations (in cellular processes, drug stability, cell organelles preferences), along with existing befell in pharmacokinetics and pharmacodynamics of the known therapeutics, mainly directly linked to the route of administration 85 , and cellular transformations 86 . Last, future perspectives and keenness for the discovering of nanotheranostics and nanotherapeutics as CNS/BBB drug delivery tools and devices will a major area of research in this field.…”
Section: Nanotherapeutics For Neuropsychiatry: Healing Insightsmentioning
confidence: 99%
“…De Vries and Van der Poll (2018) Emphasizes the necessity of empowerment and training for operators to run kanban cells in a pump-engineering organization.…”
Section: Papermentioning
confidence: 99%